The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s10709-006-9136-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Japanese flounder karyotype by chromosome bandings and fluorescence in situ hybridization with DNA markers

Abstract: The chromosomes of Japanese flounder, Paralichthys olivaceus, were examined by conventional differential staining methods including G-, Q-, C-, silver (Ag)-, fluorochrome, and replication R-bandings and by fluorescence in situ hybridization (FISH) with 5S and 18S rDNAs and telomeric DNA as probes. Replication R-banding substantially made it possible to identify 24 homologous pairs by their RBG-banding pattern and relative length. Both rDNA loci were mapped to chromosome 1, where 5S and 18S rDNA loci were locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
34
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 39 publications
5
34
0
Order By: Relevance
“…The divergent locations of 5S and 45S rDNA loci seem to be the most common situation observed in most fish (Martins and Galetti 2001) and by far the most frequent distribution pattern observed in vertebrates (Suzuki et al 1996). In contrast, Fujiwara et al (2007) indicated that the 5S and 45S rDNA loci are linked on the same chromosome. Moreover, different size and fluorescence intensity of 5S rDNA and 45S rDNA were observed in both metaphases of parental species and the hybrids, and the size and fluorescence intensity can be used to discriminate the chromosome identity.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The divergent locations of 5S and 45S rDNA loci seem to be the most common situation observed in most fish (Martins and Galetti 2001) and by far the most frequent distribution pattern observed in vertebrates (Suzuki et al 1996). In contrast, Fujiwara et al (2007) indicated that the 5S and 45S rDNA loci are linked on the same chromosome. Moreover, different size and fluorescence intensity of 5S rDNA and 45S rDNA were observed in both metaphases of parental species and the hybrids, and the size and fluorescence intensity can be used to discriminate the chromosome identity.…”
Section: Discussionmentioning
confidence: 92%
“…The diversity of 5S rDNA loci have been reported in the diploid genome of different plants and animals (Lomholt et al 1995;Laura et al 2003;Fujiwara et al 2007;Morescalchi et al 2008;Kwon and Kim 2009). The 5S rDNA is often located on a single chromosome pair in fish (Pendás et al 1994;Fujiwara et al 2007;Morescalchi et al 2008;Nirchio et al 2009) and in some mammals (Suzuki et al 1996;Laura et al 2003), probably representing a more ancient condition among animal groups.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the order Tetraodontiformes, Sphoeroides greeleyi and S. spinosus possess 1 pair of 5S rDNA sites, while Cyclichthys spinosus possesses 2 pairs (Noleto et al, 2007). In the order Pleuronectiformes, Paralichthys olivaceus (Paralichthyidae) and Solea solea (Soleidae) have 1 pair of 5S rDNA sites (Libertini et al, 2002;Fujiwara et al, 2007). Presumably, the 6 pairs of 5S rDNA signals in C. semilaevis might also have been generated from chromosome rearrangement, like the 18S rDNA.…”
Section: Discussionmentioning
confidence: 99%
“…In Salmo salar (Pendas et al, 1994) and Paralichthys olivaceus (Fujiwara et al, 2007), both the major and minor rDNA have 1 pair of signals located on the same chromosomes. In Oncorhynchus mykiss (Fujiwara et al, 1998), there are 2 pairs of 5S rDNA signals, 1 of which is syntenic with 18S rDNA and the other is on X chromosomes.…”
Section: Discussionmentioning
confidence: 99%